A Handbook on the WTO TRIPS Agreement - Taubman, Antony; Wager, Hannu; Watal, Jayashree (Cambridge : Cambridge University Press, 2012)
This handbook describes the historical and legal background to the TRIPS Agreement, its role in the WTO and its institutional framework and reviews the following areas: general provisions and basic principles; copyright and related rights; trademarks; geographical indications; patents; industrial designs, layout-designs, undisclosed information and anti-competitive practices; enforcement of IPRs; dispute settlement in the context of the TRIPS Agreement; TRIPS and public health; and current TRIPS issues. It contains a guide to TRIPS notifications by WTO members and describes how to access and make use of the official documentation relating to the TRIPS Agreement and related issues. Furthermore, it includes the legal texts of the TRIPS Agreement and the relevant provisions of the WIPO conventions referred to in it, as well as subsequent relevant WTO instruments.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Intellectual property (International law); Foreign trade regulation